2008
DOI: 10.1111/j.1469-0691.2008.01951.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of rpoB mutations among multidrug-resistant Mycobacterium tuberculosis (MDRTB) strains from Thailand and development of a rapid method for mutation detection

Abstract: Since rifampicin resistance is a surrogate marker for multidrug-resistant Mycobacterium tuberculosis (MDRTB), the present study aimed to investigate rpoB mutations conferring rifampicin resistance in M. tuberculosis strains from Thailand, and to develop a rapid, inexpensive and simple PCR-based method for rapid detection of MDRTB. Overall, 267 M. tuberculosis isolates, including 143 MDRTB isolates, were investigated. Isolates of the Beijing strain predominated among the MDRTB isolates (79.1%), but accounted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
38
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
12
38
3
1
Order By: Relevance
“…Second, mutations within the RRDR of rpoB have been reported to occur in 95% or higher of the RIF-resistant isolates (9,36,54). Third, RIF resistance is an excellent surrogate marker for MDR M. tuberculosis (26,37). In the present study, six novel rpoB mutations were identified, and they all fell outside of the RRDR region of the rpoB gene.…”
Section: Discussionmentioning
confidence: 53%
“…Second, mutations within the RRDR of rpoB have been reported to occur in 95% or higher of the RIF-resistant isolates (9,36,54). Third, RIF resistance is an excellent surrogate marker for MDR M. tuberculosis (26,37). In the present study, six novel rpoB mutations were identified, and they all fell outside of the RRDR region of the rpoB gene.…”
Section: Discussionmentioning
confidence: 53%
“…Rare loci found outside the hotspot region of rpoB are associated with resistance without associated mutation known for conferring resistance (Taniguchi, 1996;Fang, 1999;Schilke, 1999;Yuen, 1999;Heep, 2001;Zhang, 2005;Rigouts, 2007;Prammananan, 2008).…”
Section: Rifampicinmentioning
confidence: 99%
“…Mutated strains in Val146Phe (Heep, 2001;Rigouts, 2007;Prammananan, 2008) show a lowlevel resistance (MIC 4 µg/ml) (Rigouts, 2007). The Ala381Val mutation (Taniguchi, 1996) is described on a strain of MIC 200, with no other mutation on the rpoB gene.…”
Section: Rifampicinmentioning
confidence: 99%
“…The assay proved to be simple, rapid, specific, and highly sensitive in tests on isolates of M. tuberculosis from New York City, Madrid (42), India, and Mexico (51). As most rifampin-resistant isolates are also resistant to isoniazid, rifampin resistance can be used as a marker for MDR M. tuberculosis (36,44,49). However, like all nucleic acid amplification-based assays for M. tuberculosis detection (15), this assay was too complex and too prone to operator errors, sample cross-contamination, and biohazards for rapid near-patient use.…”
mentioning
confidence: 99%